(3QSGdI GdfSG GdcHjQIs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3JhcdJ Ydi ehdGfG GdHGQ GdYdGe HSe Gddg GdQMef GdQMje MOhO YHOg GdEeGe SHMGfg ef CXgQ MceJg aCYLR HQjJg s
(3BNQgG (B:s
(3hEfeG bUO HPdc Ydi jOi QabkG Hef EJUd Edjg hLdGdI dge hTQakG hYRkG hGdMeO hGdTcQ ddehdi hMOg dGTQjc dg hHg CSJYjf ai cd GdCehQ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B19s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3eOQjO (B(5360) s
Keywords: (3abg GdePGgH GdCNQis